Using the World Wide Web for the cartography of technoscientific controversies - Lorenzet, Andrea (Tecnoscienza – Italian Journal of Science & Technology Studies, 2010)
The cartography of technoscientific controversies is an innovative research technique developed within STS, aimed at describing debates on science and technology. In this review, the Web is set up as a strategic resource for data collection on such disputes; more specifically, some Web-based tools are presented, which provide data and visualizations through automated procedures for mapping disputes on science and technology.